The challenges of risk society for impact assessment. Issue 11 (2nd November 2017) - Larsen, Sanne Vammen
Abstract : This paper takes its point of departure in Ulrich Beck's theory of risk society and the aspects that characterise this society. The paper puts forward a hypothesis, on which theoretical challenges the characteristics of risk society pose to impact assessment as a decision support tool; namely, the challenge of delivering assessments and predictions and the challenge of handling differences of opinion and debate. Through a case example of integration of climate change in strategic environmental assessment, the paper uses empirical evidence from a survey and a series of interviews to carry out a preliminary discussion of how the theoretical challenges are reflected in practice. The case study results show that the challenge of delivering assessments and predictions in a risk society is reflected in the current state of practice, while the challenge of handling differences of opinion and debate is not clearly reflected.